Pengaruh Kualitas Sumber Daya Manusia Dan Fleksibilitas Organisasi Terhadap Kinerja Karyawan (Studi Terhadap Paramedis Keperawatan RSUD Dr. M. Haulussy Ambon) - Harvey Hiariey (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This study aimed to analyze the effect of partial and simultaneous Quality Human Resources and Organizational Flexibility on Employee Performance (Paramedic Care) in Hospital Dr. M. Haulussy Ambon The study was carried out on RSUD dr. M. Haulussy at Kota Ambon Ambon, Maluku Province, starting in January until February 2014. Employees in the unit of analysis is the study of nursing paramedical district general hospital dr. M. Haulussy Ambon. The population of this study is the paramedical nursing at RSU dr. M. Haulussy Ambon totaling 420 people, while the samples used in this study as large as 81 people were taken using cluster sampling method.A survey of data collection through dissemination of nursing paramedic who formed the sample. Data were analyzed using multiple regression analysis method to measure the influence of large contributions or independent variables on the dependent variable, either partially or simultaneous influence of the quality of human resources and flexibility to the performance.The results showed that the variable quality of Human Resources (HR) partially positive and significant effect on hospital performance of Paramadis at dr.M.Haulussy Ambon, this means that the first hypothesis proposed in this study received. Further flexibility is partially variable positive and significant impact on the performance Paramedic, this means the second hypothesis proposed in this study received. Furthermore, the variable quality of Human Resources and Flesksibilitas simultaneously positive and significant impact on the performance dr.M. Hospital Paramedic Haulussy Ambon, this means that the third hypothesis proposed in this study received.Keywords: Kualitas Sumber Daya Manusia, Fleksibilitas Organisasi, Kinerja karyawan.